Auditoría informática para la protección de la información digital a la COAC acción y desarrollo Ltda. Ciudad de Riobamba período 2018 - Angel Polibio, Urquizo Córdova (2021)
ABSTRACT The Computer Audit is an examination that the Information Technology Department carries out to verify the internal control standards and evidence the protocols for protecting digital information. This research project was developed in the Coac Acción and Desarrollo Ltda, whose objective is to carry out a computer audit to protect digital information to the Cooperativa Acción y Desarrollo Ltda. City of Riobamba period 2018, to determine the degree of confidentiality, integrity, and availability of the information. This investigation was developed as follows: an analysis of similar research projects carried out previously to determine state of the art. The theoretical framework was also developed; the concepts related to the research topic were found. This project used the deductive method because it starts from the general to the particular, with a non-experimental design because variables are not manipulated, and a descriptive level. Within the research project, the three audit phases were developed. The first phase being the planning, where general information about the entity is obtained. The second phase is the execution, which allowed for evaluating the internal control and determining the findings. The last phase is the communication of results, where the final audit report is prepared. The research also proposed recommendations that will help the Coac establish security policies for the protection of Digital Information. Keywords: Computer audit, Digital information, Information Technology.